(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Educationis conceived as a powerful agency, which is instrumental in bringing about thedesired changes in the social and cultural life of nation. The whole process ofeducation is shaped and moulded by the human personality called the teacher whoplays a pivotal role in any system of education.